The intended and unintended consequences of remote working: Narratives from a sample of female public service managers in South Africa - Chinyamurindi, Willie Tafadzwa (Frontiers in Psychology, 2022)
The COVID-19 pandemic has affected the world of work. Stemming from this new forms of work arrangements are proposed. One such arrangement concerns the use of remote working. Scholars appeal for more empirical inquiry into such work arrangements as an unintended consequence of the COVID-19 pandemic. The study narrow focus into investigating remote working experiences from the lens of female middle managers operating within the South African public service. A qualitative research approach utilizing narrative inquiry of 23 female middle managers was used. Based on the analysed data, two broad narratives emerge as experiences of remote working. First, the participating female middle managers bemoaned the challenge of extended office hours. Remote working appeared to create no boundaries. Despite this challenge, and a second finding, remote working was praised for allowing female middle managers the opportunity for remote working. Based on the findings, interventions are proposed that impact not just the experience of being a middle manager in the public service but also strategies in dealing with remote working. A balance is needed in striving for productivity while working remotely, a balance between individual freedoms while allowing for flexibility. This is a quest that must be attained in witnessing the success of remote working.